The Palomar Transient Factory Photometric Calibration - Ofek, E; Laher, R; Law, N; Surace, J; Levitan, D; Sesar, B; Horesh, A; Poznanski, D; van Eyken, J; Kulkarni, SR; Nugent, P; Zolkower, J; et al. (2012)
The Palomar Transient Factory (PTF) provides multiple epoch imaging for a large fraction of the celestial sphere. Here, we describe the photometric calibration of the PTF data products that allows the PTF magnitudes to be related to other magnitude systems. The calibration process utilizes Sloan Digital Sky Survey (SDSS) r ∼ 16 mag point-source objects as photometric standards. During photometric conditions, this allows us to solve for the extinction coefficients and color terms and to estimate the camera illumination correction. This also enables the calibration of fields that are outside the SDSS footprint. We test the precision and repeatability of the PTF photometric calibration. Given that PTF is observing in a single filter each night, we define a PTF calibrated magnitude system for the R band and g band. We show that, in this system, ≈59% (47%) of the photometrically calibrated PTF R-band (g-band) data achieve a photometric precision of 0.02-0.04 mag and have color terms and extinction coefficients that are close to their average values. Given the objects' color, the PTF magnitude system can be converted to other systems. Moreover, a night-by-night comparison of the calibrated magnitudes of individual stars observed on multiple nights shows that they are consistent to a level of ≈0:02 mag. Most of the data that were taken under nonphotometric conditions can be calibrated relative to other epochs of the same sky footprint obtained during photometric conditions. We provide a concise guide describing how to use the PTF photometriccalibration data products, as well as the transformations between the PTF magnitude system and the SDSS and Johnson-Cousins systems. © 2012. The Astronomical Society of the Pacific. All rights reserved.